Disarmament. Publ. by the joint disarmament commission of the L.S.I. (Labour and Socialist International) and the I.F.T.U. (International Federation of trade unions
Suppl. to: International information (ZK 16049) - German ed.: Für die Abrüstung! (ZK 16050) - French ed.: Pour le désarmement! (ZK 16048) - Dutch ed.: Op voor ontwapening! (ZK 16038).